Ultra-Low Power Soil Sensor Enabling Multi-Year Battery Life - Haryono (The Indonesian Journal of Computer Science, 2026)
Soil monitoring in large and remote agricultural areas is often limited by manual observation, resulting in low data frequency and reduced decision accuracy. To overcome this, this study presents a next-generation soil sensor system designed for ultra-low power operation and extended battery life. The system utilizes a STM32WLE5CCU6 microcontroller combined with a 6-in-1 RS485 soil sensor (T-H-EC-NPK) to measure soil humidity, temperature, electrical conductivity, and nutrient levels (N, P, K). The system operates using an optimized duty cycle, remaining in deep-sleep mode at approximately 3 μA and periodically activating for a short 600 ms sensing and data transmission phase consuming around 150 mA. This approach significantly reduces average power consumption to approximately 0.028 mA. With a 4000 mAh battery and a transmission interval of one hour, the system achieves a theoretical lifetime exceeding 16 years. However, considering practical factors such as battery self-discharge, sensor overhead, and environmental conditions, the effective operational lifetime is conservatively estimated to exceed 5–10 years without battery replacement. The results demonstrate that the proposed design successfully enables long-term, maintenance-free soil monitoring, making it suitable for large-scale and remote precision agriculture applications where energy efficiency and system reliability are critical.